Assessment of Dental Hygiene Practices among Patients Attending a Family Medicine clinic in Madinah - Rajy Alanazi, Sultan; Alhaidan, Ali Yahya (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2024)
This study aims to assess dental hygiene practices among patients attending a family medicine clinic in Madinah. With the growing recognition of oral health’s role in overall health, understanding patient behaviors and practices is essential. A cross-sectional study was conducted, utilizing a structured questionnaire to collect data from 100 patients. The results revealed significant gaps in dental hygiene practices, highlighting the need for targeted interventions. The findings emphasize the importance of educational programs to improve dental health awareness and practices among patients